Pengaruh Variasi Suhu Tempering Pada Struktur Makro Material Untuk Pengelasan Material Bekas (Used Material) Dengan Material Baru - Taufan Prasetyo; Ach. Choseiri; Aurista Miftahatul Ilmah (Universitas Islam Raden Rahmat, Malang, 2024)
Annual survey is a periodic inspection process conducted once a year on ongoing ships, aimed at checking the possibility of damage to the hull of the ship. If during the annual survey process damage is found on the plates, especially the hull plates of the ship, then the plates need to be replaced. Plate replacement means removing part of the damaged plate to replace it with a new plate through cutting and welding processes. And in the welding process, there is a joining process between the new plate and the old (used) plate where both materials have different microstructures and characteristics. In this study, a heat treatment process (Pre Heat) was carried out before welding using the tempering method on the old plate with the aim of improving the microstructure and material characteristics. The tempering process was carried out using three temperature variations, namely 200°C, 300°C, and 400°C. From the test results, it was found that the suitable temperature was 200°C, which showed no defects and had the smallest average HAZ width of 1.35mm compared to 300°C, 400°C, and non-heat treatment.